Balkan Med J 2021
DOI: 10.5152/balkanmedj.2021.21135
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 RNA in Upper Respiratory Swap Samples by Pooling Method

Abstract: Background: Widespread and effective use of molecular diagnostic tests is indispensable for protecting public health and containing the severe respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. More than 1 year into the pandemic, as resources have reached a point of depletion, grouping samples in pools of certain sizes appears to be a reasonable method to reduce both the costs and the processing time without necessitating additional training, equipment, or materials. Aims: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The pooling of specimens for testing has been shown to be an effective approach to expand detection capacity, reduce per specimen costs, and shorten turnaround time (TAT). However, false-negative results are more likely due to specimen dilution after pooling [ 24 , 25 ]. Watkins et al suggested that the pooling ratio can be evaluated using the community positivity rate.…”
Section: Discussionmentioning
confidence: 99%
“…The pooling of specimens for testing has been shown to be an effective approach to expand detection capacity, reduce per specimen costs, and shorten turnaround time (TAT). However, false-negative results are more likely due to specimen dilution after pooling [ 24 , 25 ]. Watkins et al suggested that the pooling ratio can be evaluated using the community positivity rate.…”
Section: Discussionmentioning
confidence: 99%
“…The study included all children who required HFNC upon admission or during follow-up. Patients were split into two groups: Group 1 included the patients who tested positive for SARS-CoV-2, group 2 included the patients who tested and found negative for SARS-CoV-2 COVID-19 infection was diagnosed using quantitative real-time reverse transcriptase-PCR positivity with detection of double targets, N-gene and ORF ab1 region at cycling threshold value under 35 cycles [SARS-CoV-2 (2019-nCoV) qPCR Detection Kit, Bio-Speedy, Turkey] [11]. The respiratory viruses were detected using a multiplex real-time PCR test (Bosphore Respiratory Pathogens Panel Kit V4,Anato lia Geneworks, Turkey) that is capable of identifying viral pathogens including in uenza viruses (in uenza A, pandemic H1N1 in uenza A, seasonal H1N1 in uenza A, and in uenza B), parain uenza viruses (PIVs; PIV-1, PIV-2, PIV-3, and PIV-4), human coronaviruses (CoV OC43, CoV NL63, CoV HKU1, and CoV 229E), RSV A/B, rhinovirus, hMPV, enterovirus, bocavirus, adenovirus, and parechovirus.…”
Section: Material-methodsmentioning
confidence: 99%
“…The rate of invalid samples/total samples by RT-qPCR in the routine of our lab is 1.3%, and considering that ddPCR is more resistant to inhibitors, this percentage may be even lower. Nevertheless, this problem arises in every pool testing diagnostic strategy and recommendations are to pay special attention to adequate sample collection so that pre-analytical processes do not lead to major signal losses [36,44]. Then, if we take into consideration that pooling by ddPCR is thought for screening, this has an even less negative connotation.…”
Section: Plos Onementioning
confidence: 99%